2003
DOI: 10.1001/archneur.60.12.1680
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of Parkinson Disease

Abstract: Parkinson disease (PD) is a progressive degenerative neurological disorder characterized by resting tremor, bradykinesia, cogwheel rigidity, and postural instability.1 In the later stages, approximately 25% or more of patients develop cognitive compromise. The cardinal pathological features of PD are degeneration of dopaminergic neurons in the substantia nigra pars compacta and their axons, which project principally to the caudate and putamen, and the presence of eosinophilic intracytoplasmic inclusions, Lewy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…Currently, approved treatment modalities for PD remain only palliative (Shults, 2003). We previously demonstrated that attenuation of microglial responses and adoptive transfer of Cop-1-specific immune cells into MPTP-treated animals can achieve glial expres- Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, approved treatment modalities for PD remain only palliative (Shults, 2003). We previously demonstrated that attenuation of microglial responses and adoptive transfer of Cop-1-specific immune cells into MPTP-treated animals can achieve glial expres- Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…1 Its anti-Parkinson properties also make it useful for the management of Parkinson disease. 2 There have been 3 cases of amantadine-associated corneal edema reported in the literature. [3][4][5] In each patient, bilateral corneal edema resolved within days to weeks after discontinuing the medication.…”
mentioning
confidence: 99%
“…PD treatment has largely involved strategies to correct the underlying dopamine deficit. However, management of patients with long standing disease is often complicated by development of cognitive and behavioral symptoms, resulting from medication side effects and/or development of extranigral disease, which may involve other neurotransmitter systems than dopamine (Tanner 2000;Shults 2003;Lang 2007). Neuropsychiatric symptoms that have been associated with PD therapy include hallucinations, depression, confusion, impulse control disorders, sleep disorders, daytime somnolence, and sleep attacks.…”
Section: Effect Of Rasagiline On Cognitive and Behavioral Symptoms In Pdmentioning
confidence: 99%